The perception of Buddhists on Islam and Muslims in Rusamilan, Pattani Province, South of Thailand : a case study - Rusnee Dunthara (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The unrest in southern Thailand particularly in Pattani was stirred up from time to time. The reasons of the conflicts vary from economic deprivation, political problems, cultures and religious differences and the misunderstanding between Muslims and Buddhists in the area. The investigation of the perceptions between the two religious identities; Malay Muslims and Thai Buddhists is very important. Thus the main objective of this study is to examine the Buddhists' perception of Islam and Muslims in Rusamilan, Pattani southern Thailand. The methods adopted in the study are library research and field study. The library study depends on textual analysis where the primary and secondly sources in English, Arabic, Thai, and Malay languages were consulted. Using a convenience sampling technique, a total of one hundred respondents were drawn from Buddhists in Rusamilan district, Pattani. The result showed that the perception of Islam and Muslims among Buddhists in Rusamilan is a positive perception. Majority of Buddhist respondents, ninety percent above knew Islamic features, Islamic rituals and Muslims behaviours. Beside the interaction, the result showed that Buddhist in Rusamilan have a good interaction with Muslims. Most of them have Muslims friends and always spend times together, they try to learn Malay language to communicate with Muslims in the area, and always have consultations with Muslims on Islamic issues, to gain knowledge about Islam and Muslims.